The social sciences in research - Gutiérrez Gómez, Edgar (2021)
The obvious denaturation of social settings in different parts of the world is undeniable. In all stages of humanity, only the social phenomenon was interpreted, detracting from the essence of the problems that afflict and require concrete solutions. In the absence of research and investment in the social sciences in Peru and other parts of the world, a distorted appreciation of reality is generated.